Castang and Novartis Foundation Conference on Undernutrition in Children with Cerebral Palsy: Survey of participants about decision-making for enteral (gastrostomy) feeding - Worley, G; Stevenson, R; Rosenbloom, L; Sullivan, P (2007)
Purpose. Undernutrition is a prevalent and serious problem in children with cerebral palsy (CP) who have severe cognitive and motor impairment. Decision-making concerning the initiation of enteral (gastrostomy) feeding is complex, for many reasons. The Castang and Novartis Foundations convened a meeting to present research pertinent to the management of undernutrition in children with CP. The meeting was held in London on 5 and 6 February 2004. Methods. Twenty-five participants representing the disciplines usually involved in decision-making about the need for enteral feeding came from 11 countries on 4 continents. Conference participants had a mean of 16.5 years of experience treating undernutrition in children with CP. To ascertain the opinion of participants about management issues, a case-based format was used. Cases were briefly presented and questions about them addressed important issues in decision-making about instituting enteral feeding. Opinions were based on clinical experience and knowledge of the pertinent literature. Results. There were five consensus opinions, with 90% of participants agreeing that: (1) Weight and height should be plotted on growth charts at each visit and that a subjective assessment of nutritional state and growth trajectories should be made. (2) Undernutrition severe enough to result in diminished subcutaneous fat with or without muscle wasting results in adverse health consequences. (3) The initiation of enteral feeding in children with CP results in weight gain, reduces adverse consequences of undernutrition, improves the quality of life of children, and improves the quality of life of caregivers. (4) The effect of enteral feeding on longevity (lifespan) is not known. (5) A decision by parents to provide only palliative care for a child with life-threatening undernutrition is unethical and that in such a situation reporting parents to civil authorities for child neglect would be necessary. There was a majority opinion (60-90% of conference participants agreeing) that parents should have the right to defer enteral feeding if the severity of nutrition is not thought to be life-threatening. No participant knew of a legal precedent in his or her country that ordered the initiation of enteral feeding in a child with CP, over parental refusal. Among physicians, there was no agreement about any indication or contraindication for performing an anti-reflux procedure at the time of gastrostomy in undernourished children with CP. Conclusions. For no issue is the relevant literature sufficient to provide a 'standard of care' or a 'guideline for care' for the management of undernutrition in children with CP. Therefore, this survey cannot be used for medical-legal purposes. This survey was intended to provide guidance to clinicians until there is more evidence in the literature. © 2007 Taylor and Francis.